Implementation of Environmental Management Accounting and Energy Efficiency for Green Economy Achievements in the Textile Industry in Indonesia - Kumalawati, Lely; Sudarma, Made; Rahman, Aulia Fuad; Iqbal, Syaiful (International Journal of Energy Economics and Policy, 2023)
This paper aims to examine the conceptual framework that describes the relationship between environmental management accounting, energy efficiency and green economy outcomes. In this paper, the authors argue that environmental management accounting and energy efficiency can directly influence the achievement of a green economy. This paper examines survey responses of top management in an East Java textile company registered with the Indonesian Central Bureau of Statistics. The time horizon for data collection is cross-sectional. The hypothesis was tested using a multiple linear regression analysis approach, by interpreting the regression model through the significance coefficient value to see the partial effect. In general, the proposed framework obtains adequate fit statistical results. Furthermore, the results support the argument that there is a positive and significant effect of environmental management accounting and energy efficiency on achieving a company's green economy. The limitations of this study relate to the small sample size, because environmental results and energy use are still considered confidential by many companies in Indonesia. These results can be a specific reference for policy making in companies to continue to support the achievement of green economy goals in Indonesia. This study contributes to the accounting literature, particularly in the mechanism of environmental management accounting information through empirical evidence.